Influence of initial operating conditions on technological function parameters of servicing systems - machines and devices - Ugljesa Bugaric; Milan Vugdelija; Dusan Petrovic; Dusan Glisic; Zoran Petrovic (Tehnički Vjesnik, 2017)
In warehousing and production systems, every device or machine re-commissioning after malfunction or at the start of a new shift, leads to their non-stationary operating regime caused by a certain number of residual unprocessed units. In warehouse systems, non-stationary operating regime is common when palletized goods are stored in one (two) shifts while their production runs in two (three) shifts. Such situations influence technological function parameters (TFPs) of production or warehousing systems. On the other hand, non-stationary operating regime of a single device or machine may be modelled as a single server servicing system with a finite waiting room – M/M/1/K. As a result, general analytical integration constants expression was derived based on initial arbitrary system state probability values. Influence of initial non-stationary operating regime and its duration on warehousing system TFPs is evaluated in view of the operating conditions of an existing high bay pallet warehouse.